Deontological Dilemma Response Tendencies and Sensorimotor Representations of Harm to Others - Christov-Moore, Leonardo; Conway, Paul; Iacoboni, Marco (Frontiers in Integrative Neuroscience, 2017)
The dual process model of moral decision-making suggests that decisions to reject causing harm on moral dilemmas (where causing harm saves lives) reflect concern for others. Recently, some theorists have suggested such decisions actually reflect self-focused concern about causing harm, rather than witnessing others suffering. We examined brain activity while participants witnessed needles pierce another person’s hand, versus similar non-painful stimuli. More than a month later, participants completed moral dilemmas where causing harm either did or did not maximize outcomes. We employed process dissociation to independently assess harm-rejection (deontological) and outcome-maximization (utilitarian) response tendencies. Activity in the posterior inferior frontal cortex (pIFC) while participants witnessed others in pain predicted deontological, but not utilitarian, response tendencies. Previous brain stimulation studies have shown that the pIFC seems crucial for sensorimotor representations of observed harm. Hence, these finding suggest that deontological response tendencies reflect genuine other-oriented concern grounded in sensorimotor representations of harm.